A Study of Wireless Body Area Networks and its Routing Protocols for Healthcare Environment - Kaur, Ramanpreet; Pasricha, Ruchi; Kaur, Bikrampal (Recent Advances in Electrical & Electronic Engineering, 2020)
Background: The increased cost of treatments in the health care industry and advancements in technologies have led to a promising area of development in Wireless Sensor Networks and semiconductor technologies. Wireless Body Area Networks is a subset of WSN in which sensor nodes are placed on the human body or implanted inside the body to determine various physical parameters of the human body. This information is forwarded to the medical centers or central servers through gateways. The direct advantage of this technology is the existence of portable health monitoring applications as well as location independent monitoring applications. But, still, the existence of smart hospitals needs a lot of focused research related to practical problems faced by patients as well as practitioners. Introduction: The aim of this paper is to present an essential depiction of WBAN development in both medical and non- medical applications. The important features of various wireless technologies supported by WBAN have also been presented. It is apparent that to determine the overall performance of a network in terms of different parameters like temperature, power consumption, throughput and delay, etc., a significant role is played by the routing protocols. Since WBAN directly deals with the human body and hence implementation of a new protocol is a challenging task before researchers, this paper reviews each category of routing protocols and their corresponding limitations. A comparison among routing protocols will guide researchers in implementing a specific protocol for targeted application. The paper also focuses on the future of WBAN which will provide the research areas for further exploration. Conclusion: It is found that QoS aware protocols are employed specifically for critical applications. If we consider radiation imparted from the sensors and tissue protection of the human body, the thermal aware routing protocol is the solution. Another important conclusion of this paper is that the various protocols do not provide an optimal solution for selecting the forward node during routing and this solution primarily depends on the residual energy of the nodes and distance of the node from the sink. A study of protocols developed from 2004 onwards till date shows that implementation of WBAN using integration of IoT, EoT, and fog computing has been the emerging topic of research in recent years.
Keywords: routing protocols